A study of medicinal plants used by Bajau community in Kinarut coastal area, Sabah / Nurul Alezza Hazra Munirah Alimat - Alimat, Nurul Alezza Hazra Munirah (2016)
This study focuses on identify and construct the dichotomous key of medicinal plant and determine the Bio-economic Index of the medicinal plant used by the Bajau ethnic in Kinarut Coastal Area. Semi-interview and standard collecting methods for the medicinal plant was conducted followed by the preparation of voucher specimen and identification. Dichotomous key was constructed for a well-organized flowchart identification. About 50 plant species was recorded, 35 families and 47 genera. The main families of the species that recorded are Zingiberaceae (4 species, 8%) followed by Poaceae, Fabaceae and Euphorbiaceae (3 species each, 6%). Most of the plant used to treat hypertension and decoction process is the main method in preparing the medication. Mainly part of plant used is leaf and taken through oral. The 50 plant species are under 1 phylum (Magnoliophyta) and grouped into 2 class (Magnoliopsida and Liliopsida). Minyak Serai Wangi shows the highest Bio-economic Index of total quantity traded.